Druga wojna światowa w ujęciu transnarodowym: próba poszerzenia grona odbiorców prestiżowych seriali. Przypadek Świata w ogniu (BBC/PBS, 2019‒2023) - Durys, Elżbieta; Rydzewska, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The current state of high-end television drama provides the starting point for analysing World on Fire (BBC/PBS, 2019‒2023) as an example of expanding the audience for historical series about the Second World War. The article argues that the series’ creator, Peter Bowker, employs three strategies to enhance its transnational appeal. First, World on Fire broadens the traditional national perspective on historical events by incorporating the viewpoints of other nations. Second, it introduces perspectives that have often been marginalised, including those of women, LGBTQ+ communities, and people with disabilities. Third, it uses distinct cinematic and televisual styles to depict different locations, appealing to audiences interested in cultural tourism. In doing so, the article suggests new approaches for analysing historical television drama beyond those previously adopted.